Regularity of Functions on the Reduced Quaternion Field in Clifford Analysis - Ji Eun Kim; Su Jin Lim; Kwang Ho Shon (Abstract and Applied Analysis)
We define a new hypercomplex structure of ℝ3 and a regular function with values in that structure. From the properties of regular functions, we research the exponential function on the reduced quaternion field and represent the corresponding Cauchy-Riemann equations in hypercomplex structures of ℝ3.